Resinas compostas indiretas: cerômeros - Couto, Lorenna Luísa Carvalhais [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Due to growing demand for aesthetic treatments for patients, the esthetic restorations are increasingly part of day-to-day dental surgeon. Thus, the materials and techniques have been restored stream. The indirect composite resins for special attention due to its characteristics able to solve problems found in ceramic restorations and conventional resins. They are very used to situations of great dental destruction, as well as small dental absences. These resins conventional indirect ceromer called, have a high density of inorganic particles when compared to traditional resins. Most systems use ceromer polymerization which results in higher flexural strength, minimal polymerization shrinkage rate of wear similar to enamel and color stability. Due to these properties, new systems of indirect resin restoration in occlusal restorations were successful in being increasingly used in fixed prosthodontics, such as inlays, onlays, metal free adhesive, veneers, crowns metal free and viable alternative to esthetic restorations in the porcelain when their use is contraindicated. The paper will present the most widely used methods, their indications and sequence o clinical procedures

Devido à crescente busca por tratamentos estéticos por parte dos pacientes, as restaurações estéticas fazem parte cada vez mais do dia-a-dia do cirurgião dentista. Dessa forma, os materiais e técnicas restaurados vêm sendo aperfeiçoadas. As resinas compostas indiretas recebem uma atenção especial devido às suas características capazes de solucionar problemas presentes nas restaurações de cerâmica e resinas convencionais. São muito usadas para situações de grande destruição dental, assim como em pequenas ausências dentais. Essas resinas indiretas denominadas cerômeros, apresentam alta densidade de partículas inorgânicas quando comparadas com as resinas tradicionais. A maioria dos cerômeros utiliza sistemas de polimerização que resulta em resistência flexural superior, mínima contração de polimerização, proporção de desgaste semelhante ao esmalte dental e estabilidade de cor. Devido a essas propriedades, os novos sistemas de restauração em resina indireta apresentam sucesso em restaurações oclusais, sendo cada vez mais utilizadas em prótese fixa, como inlays, onlays, adesivas metal-free, veneers, coroas unitárias livres de metal, bem como alternativa viável para as restaurações estéticas em porcelanas quando seu uso está contra-indicado. O trabalho apresentará os sistemas mais utilizados, suas indicações e seqüência de procedimentos clínicos
Keywords: Polimerização; Resinas compostas; Estética dentária; Polymerization